Factors Influencing Customers’ Purchasing Behavior and Satisfaction in Pizza Hut - Kok Ban Teoh; Miguel Cordova; Nana Nur Hasanah; A.A. Gde Satia Utama; Ainin Syazana; Daisy Mui Hung Kee; Alif Azrul; Amirul Raziq; Bing Lin Ang (Global Academia Publisher, 2021)
Fast food restaurants are prominent in many countries and they emphasize factors that can influence their customers’ purchasing behavior and boost their satisfaction of dining in and ordering online from their restaurants. The purpose of this study is to identify the factors that are influencing customers’ purchasing behavior and satisfaction in Pizza Hut to provide useful advice to the business to assist the management in planning their strategies. The research was conducted through primary data sources such as surveys and secondary data sources such as website research. The participants in the survey totaled 106 Pizza Hut customers from Malaysia and Indonesia. The results of this study were Pizza Hut customers’ behavior is influenced by cultural factors, environmental and family factors, promotional and marketing factors, promotional price factors, and lifestyle factors while customers’ satisfaction is influenced by the variety of menu options, availability of payment methods, ease of navigation on the website, the service quality and other factors. They are helpful for the company to implement strategies to grasp customers’ attention and improve its performance.